The Utilization Pattern of Capture Fisheries in the Limited Utilization Zone of the Gili Matra Marine Protected Area in West Nusa Tenggara Province - Rowi Ashari; Soraya Gigentika; Sitti Hilyana; Martanina Martanina (Jurnal Perikanan dan Kelautan, 2024)
location for capture fisheries activities. However, the management has not yet assessed the area's utilization for capture fisheries activities, necessitating research on the utilization pattern of capture fisheries in the Gili Matra conservation area. This research aims to identify the types of fishing gear used and analyze the size of the dominant fish caught in the Gili Matra marine protected area. This research was conducted from February to April 2024. Data were collected through interviews with respondents and by measuring the length of the fish. The respondents in this study were groups of fishermen who caught fish within the limited utilization zone, selected using the accidental sampling method. The number of fish samples measured in this study was 30 individuals for each fish species. The fish species measured were the dominant species caught in the Gili Matra marine protected area. The data were analyzed using descriptive analysis and length frequency analysis. The study results showed fishermen use bottom handlines, gillnets, and spearguns to catch fish within the limited utilization zone in the Gili Matra marine protected area. The dominant fish species caught in the area were Lutjanus gibbus, Siganus virgatus, and Parepeneus indicus. Almost all of these fish species had capture sizes larger than the length at first maturity.